Effective Leadership in Improving the Quality of Education in Madrasah Tsnawiyah - Musrifah; Ali Shah, Syed Ahmad; Rokhman, Mauhibur; Aprilianto, Andika (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2024)
The challenges faced by educational institutions in improving the quality of education and human resources require effective leadership strategies. This research focuses on the efforts of the principal at MTs Nurul Hidayah Tegalsiwalan Probolinggo to address issues related to curriculum objectives, teaching staff, methodologies, facilities, and evaluations. The study explores how the principal's leadership enhances teacher professionalism, facilities, learning quality, and student achievement. A qualitative approach with a case study method was employed to provide an in-depth analysis of the principal's leadership role. Data collection included interviews, observations, and documentation, with humans as the primary research instrument. Following Denzin and Lincoln's framework, the study was conducted naturally to interpret phenomena through descriptive data and inductive analysis. The findings indicate that the principal effectively fulfils multiple roles—educator, manager, administrator, supervisor, leader, innovator, and motivator—while demonstrating a charismatic and authoritative leadership style, strong managerial skills, effective communication, and a flexible approach. Supporting factors include leadership qualities and collaboration while inhibiting factors involve inadequate facilities, limited institutional support, and insufficient managerial training. The study recommends prioritizing leadership development programs, enhanced resource allocation, and infrastructure improvements to overcome barriers. Future research should investigate technology integration in leadership practices and strategies for fostering sustainable educational quality in similar contexts.